2020
DOI: 10.1038/s41598-020-60137-9
|View full text |Cite
|
Sign up to set email alerts
|

Disease asymmetry and hyperautofluorescent ring shape in retinitis pigmentosa patients

Abstract: Retinitis pigmentosa (RP) is described as a bilateral disease with inter-eye symmetry that presents on short-wavelength fundus autofluorescence (SW-AF) imaging with hyperautofluorescent (hyperAF) rings with an ellipsoid shape and regular borders. Nevertheless, both asymmetry and irregular ring morphologies are also observed. In this retrospective study of 168 RP patients, we characterize the degree of inter-eye asymmetry and frequency of irregular hyperAF ring morphologies according to mode of inheritance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…AF examination revealed a hyper-AF ring at the perifovea and various island-shaped hypo-AF dots at the periphery. The AF findings of RP vary according to genotype, but most cases show a perifoveal ringshaped hyper-AF lesion [35] similar to our present results. The lesions imaged by OCT demonstrated that hyper-AF lesions exhibited ellipsoid zone loss and an external limiting membrane [36].…”
Section: Discussionsupporting
confidence: 91%
“…AF examination revealed a hyper-AF ring at the perifovea and various island-shaped hypo-AF dots at the periphery. The AF findings of RP vary according to genotype, but most cases show a perifoveal ringshaped hyper-AF lesion [35] similar to our present results. The lesions imaged by OCT demonstrated that hyper-AF lesions exhibited ellipsoid zone loss and an external limiting membrane [36].…”
Section: Discussionsupporting
confidence: 91%
“…Evidence of this variant was found through detailed manual review of the ES reads and was only clearly identified with GS. The RCD phenotype of these patients is consistent with the one associated with PDE6B in the literature, and it matches with the phenotype of patients harboring the known p.Asn643Glyfs*29 variant (Shen et al 2014;Ellingford et al 2016;Haer-Wigman et al 2017;Carss et al 2017;Jespersgaard et al 2019;Khateb et al 2019;Jauregui et al 2020;Weisschuh et al 2020;Kuehlewein et al 2021).…”
Section: Discussionsupporting
confidence: 85%
“…Exome sequencing (ES) analysis of affected twins initially detected only one heterozygous pathogenic variant in PDE6B, c.1923_1969delinsTCTGGG, resulting in a frameshift and premature stop codon formation (p.Asn643Glyfs*29) within the phosphodiesterase catalytic domain (Table 1). This variant was absent in gnomAD and previously reported in several IRD patients (Supplemental Table S1) (Shen et al 2014;Ellingford et al 2016;Haer-Wigman et al 2017;Carss et al 2017;Jespersgaard et al 2019;Khateb et al 2019;Jauregui et al 2020;Weisschuh et al 2020;Kuehlewein et al 2021). We have classified it as pathogenic according to the American College of Medical Genetics and Genomics (ACMG) and the Association for Molecular Pathology (AMP) guidelines using the following criteria (loss-of-function variant, PVS1, detected in trans with a pathogenic variant, PM3, absent in population databases, PM2_SUPP) (Table 1).…”
Section: Detection Of a Novel Large Pde6b Deletionsupporting
confidence: 72%
“…Asymmetric disease presentation has been recognized in 3.7–14% of nsRP cases. Both Jauregui et al [5] and Sujirakul et al [3] reported that disease asymmetry was highest in AD-RP, especially in association with RP1 and RHO disease-causing variants. In our cohort, asymmetric disease presentation was observed in 3.2% and 6.1% of cases in groups 1 and 2, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These changes are usually bilateral with a high degree of inter-eye symmetry [3]. However, phenotypic variability is common, and several atypical RP phenotypes have been described, including unilateral or asymmetric cases [3][4][5]. One contributing factor is genetic heterogeneity, but the influence of disease modifiers cannot be excluded in face of the variable expressivity observed both between and within families.…”
Section: Introductionmentioning
confidence: 99%